Electronic Structure and Band Alignments of Various Phases of Titania Using the Self-Consistent Hybrid Density Functional and DFT+U Methods - Kim, Won June; Han, Myung Hoon; Lebègue, Sébastien; Lee, Eok Kyun; Kim, Hyungjun (Frontiers in Chemistry, 2019)
To understand, and thereby rationally optimize photoactive interfaces, it is of prime importance to elucidate the electronic structures and band alignments of the interfaces. For the first-principles investigation of these properties, conventional density functional theory (DFT) needs a remedy to mitigate its well-known bandgap underestimation problem. Hybrid functional and Hubbard U correction are computationally efficient methods to overcome this limitation; however, the results are largely dependent on the choice of parameters. In this study, we employ recently developed self-consistent approaches, which enable non-empirical determination of the parameters, to investigate TiO2 interfacial systems – the most prototypical photocatalytic systems. We investigate the structural, electronic, and optical properties of rutile and anatase phases of TiO2. We find that the self-consistent hybrid functional predicts the most reliable structural and electronic properties that are comparable to the experimental and high-level GW results. Using the validated self-consistent hybrid functional method, we further investigate the band edge positions between rutile and anatase surfaces in vacuum and in an electrolyte medium by coupling with the Poisson-Boltzmann theory. This suggests the possibility of a transition from the straddling-type to the staggered-type band alignment between rutile and anatase phases in the electrolyte medium, which is manifested by the formation of a Stern-like layer at the interfaces. Our study not only confirms the efficacy of the self-consistent hybrid functional method in reliably predicting the electronic structure of photoactive interfaces, but also elucidates a potentially dramatic change in the band edge positions of TiO2 in aqueous electrolyte medium which can extensively affect its photophysical properties.